2012
DOI: 10.1524/ncrs.2012.0199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of a new mercury(II) chlorine complex with nitronyl nitroxides, C15H19Cl4Hg2N4O2

Abstract: C 15 H 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, 2009(Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. non-polymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al, 2012;Lou et al, 2012;Zhu et al, 2009;Carballo et al, 1993;Yan et al, 2012;Hu et al, 2012Hu et al, , 2015Ding et al, 2012;Matthews et al, 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, 2009(Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. non-polymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al, 2012;Lou et al, 2012;Zhu et al, 2009;Carballo et al, 1993;Yan et al, 2012;Hu et al, 2012Hu et al, , 2015Ding et al, 2012;Matthews et al, 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A survey of the structural investigations of mercury halide complexes with benzimidazole derivatives has shown that they come in two main types; polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et al, , 2011Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or discrete molecules, i.e. nonpolymeric (Xiao et al, 2011;Wu et al, 2009;Zhao et al ., 1998;Manjunatha et al, 2011;Wang et al, 2007Wang et al, , 2009Wang et al, , 2012Wang et al, , 2015Chen et al, 2014;Su et al, 2003;Quiroz-Castro et al, 2000;Yang & Luo, 2012;He et al, 2012;Bouchouit et al, 2015).…”
Section: Database Surveymentioning
confidence: 99%